BUBBLE GROWTH IN SLIGHTLY SUPERSATURATED ALBITE MELT AT CONSTANT PRESSURE - Baker D.R.; Robert G.; Allard E.; Bai L.; Lang P.; Bergevin J.-F. (My University, 2006)
Bubble growth experiments were performed in a piston-cylinder by hydrating albite melt with ~11 wt.% H2O at 550 MPa followed by rapid decompression at 1 MPa s-1 to pressures of 450 or 400 MPa. At these conditions the melt was supersaturated with ~0.5 or ~1.5 wt.% H2O, respectively, which caused rapid exsolution and bubble growth. Results at 1200 °C demonstrate that portions of the initial cumulative bubble-area distributions may be characterized by a power law with an exponent near 1, but they rapidly evolve to exponential distributions and approach a unimodal distribution after 32 h of growth. This evolution occurs by the growth of larger bubbles at the expense of smaller ones. The growth rate of the average bubble radius in these experiments is described by a power law whose exponent is 0.35, close to the theoretical exponent of 1/3 for phase growth in which coalescence is dominated by Ostwald ripening of the bubbles. Over the range of pressures and water contents investigated at 1200 °C, the bubble-size distributions and growth rate are not significantly affected by changes in the amount of exsolved water or by splitting the decompression path into two steps. Similar decompression experiments at 800 °C are dominated by smaller bubbles than in the 1200 °C experiments and also demonstrate exponential cumulative size distributions, but consistently contain a small fraction of larger bubbles. The growth rate of these bubble radii cannot be fit with a power law, but a logarithmic dependence of the bubble radii on time is possible, suggesting a difference in the growth mechanisms at low and high temperatures. This difference is attributed to the orders of magnitude changes in melt viscosity and water diffusion in the melt as the temperature varies from 800 to 1200 °C. At 1200 °C the transport properties of albite melt resemble those of natural basaltic melts whereas at 800 °C the properties are similar to those of andesitic to dacitic melts. The decompression rate used in this study exceeds natural rates by one to two orders of magnitude. Thus, these results indicate that natural mafic-to-intermediate magmas supersaturated with only a small excess of water should easily nucleate bubbles during ascent and that bubble growth in mafic magmas will proceed much more rapidly than in andesitic to dacitic magmas. Intermediate composition magmas also may be capable of forming bimodal bubble-size distributions even in the case when only one nucleation event occurred. The rapid evolution of the bubble-size distribution from a power law to an exponential may be useful in constraining the time duration between bubble nucleation and the quenching of natural samples. © 2006 Elsevier Inc. All rights reserved.